Tourism Villages: Developing Tourist Attractions Based on Environmental Conservation for Sustainable Tourism - GEE, Sonia; LISTYORINI, Haniek (PT Keberlanjutan Strategis Indonesia, 2025)
Tourism villages are tourism activities that are considered as a means of preserving nature and cultural heritage of certain communities. Tourism villages are considered to be able to create sustainable tourism that is beneficial to the local community. This researcher aims to explain the form of development of environmentally friendly tourist attractions in Asinan Tourism Village and its contribution to sustainable tourism. The research method uses qualitative research with data collected through informants, observation and document studies. The data is analyzed through an inductive process to be able to draw a number of conclusions. The results of the study stated that the development of tourist attractions in Asinan Village relies on the wealth of environmental resources, both the natural environment, socio-culture and the economy of the swamp fishing community. Tourism attractions based on the swamp environment include natural tourism, cultural tourism typical of swamp fishermen, artificial tourism, culinary tourism, and educational tourism. Managed tourist attractions play a role in the preservation of the natural environment, cultural environment, economic environment and community empowerment.